2021
DOI: 10.1038/s41598-021-94264-8
|View full text |Cite
|
Sign up to set email alerts
|

A phosphate and calcium-enriched diet promotes progression of 5/6-nephrectomy-induced chronic kidney disease in C57BL/6 mice

Abstract: C57BL/6 mice are known to be rather resistant to the induction of experimental chronic kidney disease (CKD) by 5/6-nephrectomy (5/6-Nx). Here, we sought to characterize the development of CKD and its cardiac and skeletal sequelae during the first three months after 5/6-Nx in C57BL/6 mice fed a calcium- and phosphate enriched diet (CPD) with a balanced calcium/phosphate ratio. 5/6-NX mice on CPD showed increased renal fibrosis and a more pronounced decrease in glomerular filtration rate when compared to 5/6-Nx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Next, we examined two major regulators of arterial stiffness and vascular tone, the renin–angiotensin–aldosterone system (RAAS) and the sympathetic nervous system in our model of dietary phosphate excess. We reported previously that CKD mice fed the CPD have higher aldosterone levels compared with CKD mice on ND [ 32 ]. Besides the fact that the RAAS is a known regulator of blood pressure and vascular tone, it has been suggested that the RAAS is also an important determinant of arterial stiffness [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we examined two major regulators of arterial stiffness and vascular tone, the renin–angiotensin–aldosterone system (RAAS) and the sympathetic nervous system in our model of dietary phosphate excess. We reported previously that CKD mice fed the CPD have higher aldosterone levels compared with CKD mice on ND [ 32 ]. Besides the fact that the RAAS is a known regulator of blood pressure and vascular tone, it has been suggested that the RAAS is also an important determinant of arterial stiffness [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similar biochemical and skeletal changes have been reported in other CKD mouse models, including 5/6 nephrectomy model (5/6Nx), EC injury models, dietary induction/exacerbation, and transgenic models, as well as AD–CKD rat models. [ 28,45‐50 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar biochemical and skeletal changes have been reported in other CKD mouse models, including 5/6 nephrectomy model (5/6Nx), EC injury models, dietary induction/exacerbation, and transgenic models, as well as AD-CKD rat models. [28,[45][46][47][48][49][50] The changes from AD-CKD were consistently achieved with less than 2 months of treatment; conversely, 5/6Nx and EC models typically require longer periods of time and invasive surgeries that are accompanied by several limitations, including an increased risk of injury and mortality, alterations related to surgical ablation rather than loss of renal function, nonreversibility of the condition, a relatively large degree of variability, and, in some cases, the necessary use of an inducing agent (e.g., 1,25(OH) 2 D 3 ) and/or use of gene-edited mouse models to achieve biochemical changes and vascular calcification. [24,25] As concluded in previous publications with more comprehensive analyses of the (Figure legend continued from previous page.)…”
Section: Comparison Of Adenine-induced Ckd-mbd With Other Mouse Model...mentioning
confidence: 99%
“…On the other hand, several previous studies showed that 5/6 Nx induces CKD‐related pathophysiology, including skeletal myopthy 6,7 and diminished cortical/trabecular bone microarchitecture 8,9 in C57BL/6 mice, although we have not shown the data of bone pathological features in our study. Moreover, 5/6 Nx induced renal fibrosis and decreased glomerular filtration rate in C57BL/6J mice 10,11 . We therefore believe that C57BL/6 mice could be used as a model to exhibit muscle atrophy and bone loss with the progression of CKD after 5/6 Nx.…”
mentioning
confidence: 94%
“…Moreover, 5/6 Nx induced renal fibrosis and decreased glomerular filtration rate in C57BL/6J mice. 10 , 11 We therefore believe that C57BL/6 mice could be used as a model to exhibit muscle atrophy and bone loss with the progression of CKD after 5/6 Nx. We would like to plan the study to examine myokine expression using the other CKD model mice in the near future.…”
mentioning
confidence: 99%